2002
DOI: 10.1111/1467-9620.00181
|View full text |Cite
|
Sign up to set email alerts
|

Defining Reflection: Another Look at John Dewey and Reflective Thinking

Abstract: Thinking, particularly reflective thinking or inquiry, is essential to both teachers’ and students’ learning. In the past 10 to 15 years numerous commissions, boards, and foundations as well as states and local school districts have identified reflection/inquiry as a standard toward which all teachers and students must strive. However, although the cry for accomplishment in systematic, reflective thinking is clear, it is more difficult to distinguish what systematic, reflective thinking is. There are four prob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
694
0
84

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 1,126 publications
(789 citation statements)
references
References 4 publications
11
694
0
84
Order By: Relevance
“…Dowd, Bishop, & Bensimon, 2015;Dowd, Bishop, Bensimon, & Witham, 2012;Rueda, 2012;, our theoretical frame integrates practice theory with cultural historical activity theory (CHAT). We use practice theory, which explicates how individual practitioners develop expertise to address problems of practice, to analyze what practitioners learn and do through practitioner inquiry (Kemmis & McTaggart, 2000;Reason, 1994;Rodgers, 2002) and CHAT (Engeström, 2001(Engeström, , 2008Portes & Salas, 2011;Rueda, 2012) to analyze how the learning of individuals can constitute organizational learning on behalf of their organizations (Lee, 2011;. Utilizing practice theory and CHAT together creates a multifaceted analytical lens because CHAT expands on the more individualistic lens of practice theory by placing the practices of individual practitioners in social, cultural, and historical context (Portes & Salas, 2011).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…Dowd, Bishop, & Bensimon, 2015;Dowd, Bishop, Bensimon, & Witham, 2012;Rueda, 2012;, our theoretical frame integrates practice theory with cultural historical activity theory (CHAT). We use practice theory, which explicates how individual practitioners develop expertise to address problems of practice, to analyze what practitioners learn and do through practitioner inquiry (Kemmis & McTaggart, 2000;Reason, 1994;Rodgers, 2002) and CHAT (Engeström, 2001(Engeström, , 2008Portes & Salas, 2011;Rueda, 2012) to analyze how the learning of individuals can constitute organizational learning on behalf of their organizations (Lee, 2011;. Utilizing practice theory and CHAT together creates a multifaceted analytical lens because CHAT expands on the more individualistic lens of practice theory by placing the practices of individual practitioners in social, cultural, and historical context (Portes & Salas, 2011).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…In the literature review, we synthesize studies of the use of data for organizational learning and change towards racial equity in higher education. As we discuss in our literature review, published works offer many examples of change among individuals who adopt a stronger identity as change agents through participation in action research utilizing practitioner inquiry (the systematic use of observation and data to hone one's professional expertise; Rodgers, 2002). At times, individual agency for equity has been associated with programmatic and departmental level reforms.…”
Section: Introductionmentioning
confidence: 99%
“…Habits of mind can be defined as "a set of assumptions -broad generalized, orienting predispositions that act as a filter for interpreting the meaning of experience" (Mezirow, 2000, p. 17-18). Moreover, instantaneous experimentation (e.g., thought experiments) may serve to drive and trigger reflection (e.g., Schön, 1983 and1987;Rodgers, 2002;Cope, 2003;Ramsey, 2005).…”
Section: Reflection and Reflective Questioningmentioning
confidence: 99%
“…Medicine, nursing, and pharmacy are among the disciplines that are adapting these types of reflective processes in curricula to aid in learning as well as improve patient care. [13][14][15][16][17][18][19][20][21] The extent of medical residents' reflection has been explored [13][14][15] and showed that physicians' decision-making skills were improved in complex clinical cases if they were able to critically reflect on those experiences. 15 An evaluation of nursing students concluded that interview sessions (individual, paired, and group) on reflective practice were viewed as beneficial for the participating students and encouraged them to practice reflective thinking on their own.…”
Section: Discussionmentioning
confidence: 99%
“…17 Like many other professions over the past few decades, accreditation standards for pharmacy education require student reflection and subsequent assessment of these skills. [18][19][20] Additionally, the American Society of Health-System Pharmacists Required Competency Areas, Goals, and Objectives, for Postgraduate Year One Pharmacy Residencies address the need for residents to reflect on their personal performance and professional development. 21 Published works on reflection in pharmacy center on pharmacy students, but the literature suggests reflection is necessary in the day-to-day practice of a pharmacist as well.…”
Section: Discussionmentioning
confidence: 99%